Literature Study of Spirituality in the Frail Elderly - Syiffani, Najwatul; Hadi, Nurul; Juanita, Juanita (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Frailty is the occurrence of impaired adaptation function and reduced functional. Spiritual needs are an important aspect in dealing with problems in order to adapt to the changes that occur in oneself due to the aging process. The purpose of this review is to identify the concept of spirituality in frail elderly. The literature review was conducted using Pubmed and Science Direct databases supplemented by free searches using Google Scholar from various international and national journals from 2019 to 2024. The database search query consisted of two search concepts the concept of frail elderly and the concept of spirituality. The results of this scientific paper contain several literatures that discuss the importance of strengthening the spiritual aspect in elderly people who are physically weak. As age increases, the spiritual aspect becomes important to improve the quality of life of the elderly. Fulfilling spirituality in the elderly who are physically weak helps them cope with events in their lives and feel more positive. It is expected that health workers must pay attention to spiritual needs in order to provide more integrative care.